Kekuatan Tekan dan Flexural Material Komposit Serat Bambu Epoksi - Agustinus Purna Irawan; I Wayan Sukania (Jurnal Teknik Mesin (Sinta 3), 2013)
Natural fiber composite to be one good choice to substitute synthetic fiber composite. One of the abundance of natural fiber is bamboo fiber. This study aims to develop and obtain the mechanical characteristics of bamboo fiber composite with epoxy matrix that will be implemented on the socket prosthesis product. Testing was conducted involve the compressive strength according ASTM D 695, flexural strength according ASTM D 730-03, and compressive failure test of socket prototype product according ISO 10328. Based on the results testing, obtained compressive strength of 41.44 MPa, flexural strength of 98.32 MPa, and compressive failure maximum of socket prosthesis prototype made ​​from bamboo fiber epoxy composites 87.1 ± 4.3 kN. The result show that strength of bamboo fiber epoxy composite has potential to be developed further as socket prosthesis and other engineering materials.